PERANAN NOTARIS DAN PERLINDUNGAN HUKUM TERHADAP PERUSAHAAN DALAM JAMINAN RESI GUDANG (STUDI DI PT BANUA LIMA SEJURUS) - , Lia Veronita Sbastin, Dr. Ari Hernawan, SH., M.Hum. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The research, entitled \"The Role of the Notary and Legal Protection Against Company Guarantee In Warehouse Receipt (Study at PT Banua Lima Sejurus)\" aims to determine protection by Undang-Undang No. 9 of 2011 on the company's warehouse receipt system as collateral for the right provider warehouse receipt, warehouse managers know the responsibility to guarantee that the goods are damaged or lost is not caused errors warehouse manager and find out the obligations and role of the notary in the Guarantee Agreement warehouse receipt. This research using normative empirical legal research on primary and secondary data. All data were analyzed with qualitative methods. The results showed that warehouse receipt system in Indonesia are less popular due to lack of socialization by the government , concern with profits, invest safety in warehouse receipts, and fraud in the investment of the warehouse receipt, other than that the goods are entrusted with managing the warehouse is not uncommon to experience damage both intentional or not, the warehouse receipt system is made using authentic act by notary deed granting the rights set forth in the guarantee that the warehouse receipt system is getting stronger in the eyes of the law and has the perfect strength of evidence.